DESENVOLVIMENTO E JUSTIÇA NA MISSÃO INTEGRAL: UMA ANÁLISE CRÍTICA DA PRESENÇA DA TEOLOGIA E PRÁXIS DA MISSÃO INTEGRAL NO SOLO PAULISTANO - Estudo da PIBSP. - CARVALHO, EMANUEL RUBENS DE (2015)
In the present study on the theme: "Development and Justice in Integral Mission: A critical analysis of the presence of Theology and Praxis of Integral Mission on PaulistanoSoil". I tried to analyze the presence of the concept of development and justice of Integral Mission on São Paulo soil, and for such analysis was taken as a research subject the First Baptist Church of São Paulo. This work was developed in the Post-Graduation Program in Religious Studies, and belongs to the line of research "Religion, Society and Culture". The methodology used in data collection was a bibliography review and field research through interviews. The questions that guided the research were: What is development and justice in Integral Mission? Is it posible to notice the presence of these concepts in the practice and theology of the First Baptist Church of São Paulo?After an analysis of Integral Mission and the researched church, we found the similarities and differences, as well as assumptions that justify these facts. In the first chapter it was presented the Integral Mission, History, Theology, and Method. In the second chapter the concepts of development and justice were developed. The last chapter presented the First Baptist Church of Paulo, and sought to establish a dialogue between the concept of Development and Justice of Integral Mission and theology and praxis of First Baptist Church of São Paulo.